2018
DOI: 10.1002/zaac.201800453
|View full text |Cite
|
Sign up to set email alerts
|

Argyrodite‐Type Cu8GeSe6–xTex (0 ≤ x ≤ 2): Temperature‐Dependent Crystal Structure and Thermoelectric Properties

Abstract: Substitution of Se by Te in argyrodite‐like Cu8GeSe6 leads to compounds Cu8GeSe6–xTex (0 ≤ x ≤ 2) and involves a structure change from the Cu8GeSe6 type to the Ag8GeTe6 type. The crystal structure of Cu8GeSe4.25Te1.75 between 50 °C and 500 °C reveals pronounced disorder of Cu atoms that is best described by anharmonic atomic displacement parameters using the Gram‐Charlier expansion. Diffusion pathways are visualized by isosurfaces of joint probability density functions. The lattice parameter a increases with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 68 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…30−32 When the configuration entropy is high enough, the phase transition could be shifted to even below room temperature, which results in maintaining the required crystal structure symmetry in all temperature ranges of the operation and at the same keeping improved electrical transport properties. 29,33 A series of argyrodite compounds, such as Cu 8 GeSe 6 , 34,35 Cu 7 PSe 6 , 29,36,37 Ag 9 AlSe 6 , 38 Ag 8 SnSe 6 , 39−41 Ag 9 GaSe 6 , 42−44 Ag 9 GaS 6 , 45 Ag 8 SiSe 6 , 46 Ag 8 GeSe 6 , 47 Ag 8 GeTe 6 , 48,49 and Ag 9 TlTe 5 , 50 have been demonstrated as the promising TE materials with a high ZT of 1.0 and above at high temperatures. The best reported ZT parameter for the n-type argyrodites reaches a value of ∼1.62 for Ag 8.28 Cu 0.72 GaSe 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30−32 When the configuration entropy is high enough, the phase transition could be shifted to even below room temperature, which results in maintaining the required crystal structure symmetry in all temperature ranges of the operation and at the same keeping improved electrical transport properties. 29,33 A series of argyrodite compounds, such as Cu 8 GeSe 6 , 34,35 Cu 7 PSe 6 , 29,36,37 Ag 9 AlSe 6 , 38 Ag 8 SnSe 6 , 39−41 Ag 9 GaSe 6 , 42−44 Ag 9 GaS 6 , 45 Ag 8 SiSe 6 , 46 Ag 8 GeSe 6 , 47 Ag 8 GeTe 6 , 48,49 and Ag 9 TlTe 5 , 50 have been demonstrated as the promising TE materials with a high ZT of 1.0 and above at high temperatures. The best reported ZT parameter for the n-type argyrodites reaches a value of ∼1.62 for Ag 8.28 Cu 0.72 GaSe 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A series of argyrodite compounds, such as Cu 8 GeSe 6 , , Cu 7 PSe 6 , ,, Ag 9 AlSe 6 , Ag 8 SnSe 6 , Ag 9 GaSe 6 , Ag 9 GaS 6 , Ag 8 SiSe 6 , Ag 8 GeSe 6 , Ag 8 GeTe 6 , , and Ag 9 TlTe 5 , have been demonstrated as the promising TE materials with a high ZT of 1.0 and above at high temperatures. The best reported ZT parameter for the n -type argyrodites reaches a value of ∼1.62 for Ag 8.28 Cu 0.72 GaSe 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, its band gap ( E g ) can be reduced by alloying Te . This is important as the narrowing of the band gap will enhance the carrier concentration and improve the TE performance. , Furthermore, some work has revealed that the pristine CGS has a high carrier concentration of ∼10 21 cm –3 and exhibits a metal-like conducting behavior, while some work indicates that it has a carrier concentration of only 10 17–18 cm –3 in magnitude and is a typical semiconductor . These inconsistent results suggest that it is strongly necessary to determine the carrier concentration accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Binary and more complex chalcogenides of copper and silver are valuable functional materials [1][2][3]. In particular, copper and silver chalcogenides with heavy p-elements are of interest as thermoelectric materials [4][5][6][7][8]. Several representatives of this class, due to their unique crystal structure, have ionic conductivity for Cu + or Ag + cations, which makes them very promising for use in the development of photoelectrode materials, electrochemical solar energy converters, ion-selective sensors, etc.…”
Section: Introductionmentioning
confidence: 99%